Mitigating the Impact of the Presidential Threshold’s Abolition in Indonesia: A Policy Approach - Albab, Biantara; Prasetyoningsih, Nanik; Anugrah, Alma Fuji (Jurnal Media Hukum, 2025)
The Constitutional Court's decision to eliminate the presidential candidacy threshold will change Indonesia's political and electoral system. Small parties and independent candidates have more opportunities thanks to the elimination of the presidential nomination requirement for parliamentary seats or national votes. But this decision's potential consequences must also be considered. The aim of this study is to examine the effects of removing the presidential candidacy threshold on Indonesian politics and propose solutions. The research is normative legal and uses conceptual and comparative approaches to study legal theories, principles, and concepts and compare practices in different jurisdictions. This approach allows an in-depth examination of the normative basis for abolishing the presidential threshold and its relevance and implications through comparison with other political systems. The policy encourages small parties to run in elections, but it may lead to political fragmentation and instability. The Constitutional Court's mandate for open legal policy requires policy mitigation by raising the parliamentary threshold.